De ponta a ponta: narrativas infantis e formação do leitor literário do ensino fundamental - anos iniciais - Lima, Denise Cristina Camilo de (2020)
This research has as its object of study the contribution of children's literature in the formation of critical literary readers. Based on the corpus of analysis of the works What the eyes do not see (1981) by Ruth Rocha, The princess that chose (2006) by Ana Maria Machado and Maria goes with the others (1981) by Sylvia Orthof, the objective investigation is to verify how mediation of reading children's narratives occurs in first and fifth year of Elementary School - Early Years and how it is able to contribute to the formation of the literary reader. Moreover, intends to investigate how the family’s participation can stimulate children in this dialogical process of encourage reading practice. The research was reasoned on the theoretical reflections of Zilberman, Abramovich, Todorov, Bakhtin, Colomer, Candido, Coelho, among others. The methodological procedure of the investigation was intermediated by an action research with a qualitative and quantitative approach. The participant observation in the mediated application of the didactic sequence allowed to verify how children in the beggining and at the ending of the Elementary School - Early Years dealt with the proposal of aesthetic experience involving verbal interaction with children's narratives. It may be affirmed, from the results obtained with the research, the importance of the child's contact with the oral and written literary text since the beginning of its school life to the following years, being the solidification of this base a primary factor in the process of subject's humanization and at the formation of the literary reader with reflective and critical potential. As an “Educational product”, an ebook was created, entitled Aesthetic experience with children's narratives: contribution to the formation of literary readers in Elementary School - Early Years, with a reasoned experimentation report. The free and public access to the material for professionals of Basic Education will be available on the digital platform Medium Brazil.